Heat Transfer Enhancement in Flue-Gas Systems with Radiation-Intensifying Inserts: An Analytical Approach - Justina Menkeliūnienė; Rolandas Jonynas; Linas Paukštaitis; Algimantas Balčius; Kęstutis Buinevičius (Energies)
A significant portion of energy losses in industrial systems arises from the inefficient use of high-temperature exhaust gases, emphasizing the need for enhanced heat recovery strategies. This study aims to improve energy efficiency by examining the effects of radiation-intensifying inserts on combined radiative and convective heat transfer in flue-gas heated channels. A systematic literature review revealed a research gap in understanding the interaction between these mechanisms in flue-gas heat exchangers. To address this, analytical calculations were conducted for two geometries: a radiation-intensifying plate between parallel plates and the same insert in a circular pipe. The analysis covered a range of gas-flue and wall temperatures (560–1460 K and 303–393 K, respectively), flow velocities, and spectral emissivity values. Key performance metrics included Reynolds and Nusselt numbers to assess flow resistance and heat transfer. Results indicated that flue-gas temperature has the most significant effect on total rate of heat transfer, and the insert significantly enhanced radiative heat transfer by over 60%, increasing flow resistance. A local Nusselt number minimum at a length-to-diameter ratio of approximately 26 suggested transitional flow behavior. These results provide valuable insights for the design of high-temperature heat exchangers, with future work planned to validate the findings experimentally.